REFRAMING SPANISH ADOPTION FROM CHINA: ANDREA VIGO’S PERSPECTIVE ON REPRODUCTIVE JUSTICE IN HERIDAS SIN PATRIA - Kim, Yeon-Soo (ConSecuencias, 2024)
This article explores Andrea Vigo’s Heridas sin patria (2020), marking the inaugural memoir penned by a Chinese adoptee from Spain. The central contention posited herein is that Vigo challenges the two dominant discourses surrounding the intercountry adoption of Chinese babies—colorblindness and humanitarian rescue—and reframes this as a transnational reproductive issue. By analyzing her identity crisis, which stemmed from constant racialization as an Asian woman despite being raised as a white Spaniard, her story questions colorblindness in the discourse of interracial adoption. This study also argues that Vigo’s writing is an outcry for a more inclusive and equitable society where racialized subjects like herself can feel they belong. To achieve the ideal, the author places the Spanish adoption of Chinese infants within the framework of transnational reproductive justice. Her memoir employs intertextuality by citing feminist, anti-totalitarian authors such as Woolf, Atwood, and Martín Gaite, which strengthens her stance. Keywords: transnational reproductive justice, interracial adoption, racial melancholia, China’s one-child policy, colorblindness, Chinese adoption in Spain Este ensayo explora Las heridas sin patria de Andrea Vigo, la primera memoria escrita por una adoptada china en España. Mientras Vigo se identifica como una mujer blanca española, la sociedad la percibe como asiática y por lo tanto extranjera. Este trabajo se enfoca en la discrepancia entre identificación y percepción que crea una crisis de identidad en la autora e interroga cómo su historia problematiza el daltonismo racial en el discurso de la adopción transnacional. Su escritura no debe ser entendida sólo como un ejercicio terapéutico para recuperarse de la crisis de identidad. Este estudio lee su memoria como una demanda por una sociedad más inclusiva en la que los sujetos racializados como ella pueden sentirse pertenecientes a la misma. Vigo usa la intertextualidad con citas de escritoras feministas, anti-totalitarias como Woolf, Atwood y Martín Gaite para replantear la adopción transnacional dentro del marco de la justicia reproductiva transnacional.